LESSONS LEARNED FROM THEATER CREATION FROM THE PERSPECTIVES OF CHULALONGKORN UNIVERSITY DEMONSTRATION SECONDARY SCHOOL: A CASE STUDY OF LEARNERS IN ART LEARNING ASSESSMENT PROJECT - Testhomya, Kodchakon (Fine Arts Journal: Srinakharinwirot University, 2020)
This research aims at compiling lessons learned from the theater creation of Chulalongkorn University Demonstration Secondary School students in the Arts Learning Assessment Project, which is a core concept integrated in Arts course (fundamental course) A23101 in the first semester of academic year 2019. This Arts course consists of 3 subjects: Dancing Art, Music, and Visual Art. There are 226 grade 11th students divided into 7 classes and they have to study the Dancing Art subject 1 period each week. The teacher applies Drama in Education theory (DIE) and Applied Theatre theory to the classes. The Constructivism theory and 7-step CIPPA Model are also applied to teaching methods. Based on these teaching methods, learners can appropriately integrate their prior knowledge, new knowledge, and skills together. They are also able to select the roles in accordance with their expertise. This makes teacher recognizes and acknowledges the teamwork, leadership skills, and good listener skills in learners. Additionally, the integrated learning in the Department of Arts consisting of 3 subjects (i.e. 1. Visual Arts, 2. Music, and 3. Dancing Arts) can promote learners’ global skills such as logical thinking, problem solving, communication, and technology skills. The learners can express these skills creatively according to the contexts in their daily lives. As for the Department of Art, the theater creation is regarded as one of authentic assessments enhancing learners’ necessary skills for the 21st century. It also provides opportunity for learners to discover their potential that can be applied to their daily life.